KONTRIBUSI KEPEMIMPINAN INSTRUKSIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU: STUDI PADA SEKOLAH DASAR - Septiani, Depi; Fitriadi; Riswandi; Efendi, Ujang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher performance refers to the level of success of teachers in carrying out their professional duties in accordance with their assigned field of expertise. It can be measured through teachers’ work styles in the learning process and through the results of task implementation completed within a certain period based on established performance standards. The problem addressed in this study is the low level of teacher performance in public elementary schools throughout Purbolinggo Subdistrict, East Lampung Regency. This study aims to determine the significant effect of principals’ instructional leadership on teacher performance in elementary schools. The research method used was quantitative research with a correlational approach and an ex post facto research design. The population of this study consisted of teachers in public elementary schools throughout Purbolinggo Subdistrict, East Lampung Regency, with a sample of 96 teachers selected through simple random sampling. Data were collected using questionnaires. The data were analyzed using SEM-PLS and simple regression analysis. The results show that principals’ instructional leadership has a significant effect on teacher performance in elementary schools, as indicated by a p-value < 0.05 (0.025 < 0.05). Principals’ instructional leadership contributes 5.3% to teacher performance, while the remaining percentage is influenced by other factors.